Pharmacokinetic Studies on Diazepam Using UV-Visible Spectroscopy - GUNASEKARAN, S.; THILAK KUMAR, R. (Asian Journal of Chemistry, 2010)
The aim of the present investigation is to study the bound blood-drug interaction of diazepam using UV-Vis spectroscopic method. Diazepam is an anti-epileptic drug which can be useful in the treatment of epilepsy. Bound blood-drug interaction is a method of analysis to understand the pharmacokinetic parameters with regard to the plasma drug concentration in the blood. The pharmacokinetic properties of a particular drug are basically related to its absorption, distribution, metabolism and excretion. When a drug is given, it reaches its peak level in the blood pretty quickly and the drug level then decreases as the drug is broken down and removed from the blood. UV-Vis spectral measurements have been used to study the pharmacokinetic interaction of the drug with the living system (dog as a model); the results of clinical significance have been discussed.